2018
DOI: 10.1124/dmd.118.082065
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Cytokine Levels and CYP3A4 Phenotype in Patients with Rheumatoid Arthritis

Abstract: Systemic inflammation has been linked to suppressed CYP3A4 activity. The aim of this study was to examine associations between levels of a broad selection of cytokines and CYP3A4 phenotype in patients with rheumatoid arthritis (RA). The study included 31 RA patients treated with tumor necrosis factor (TNF)- inhibitors. CYP3A4 phenotype was measured as serum concentration of 4-hydroxycholesterol (4OHC) by ultra-performance liquid chromatography-tandem mass spectrometry in samples collected prior to and 3 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…23e27 Furthermore, IL-6 was recently found to be negatively correlated with 4-bhydroxycholesterol, an endogenous marker of CYP3A activity in vivo, in patients with rheumatoid arthritis. 28 Although possibly confounded by the existing positive correlation between IL-6 and body weight, the present study supports the speculation that inflammatory status, e.g. increased IL-6 levels, may partly mediate the obesity-induced hepatic CYP3A suppression.…”
Section: Discussionsupporting
confidence: 77%
“…23e27 Furthermore, IL-6 was recently found to be negatively correlated with 4-bhydroxycholesterol, an endogenous marker of CYP3A activity in vivo, in patients with rheumatoid arthritis. 28 Although possibly confounded by the existing positive correlation between IL-6 and body weight, the present study supports the speculation that inflammatory status, e.g. increased IL-6 levels, may partly mediate the obesity-induced hepatic CYP3A suppression.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, rheumatoid arthritis patients exhibit higher plasma concentrations of simvastatin, another CYP450 substrate ( Schmitt, Kuhn, Zhang, Kivitz, & Grange, 2011 ) and lower plasma concentrations of 4-ßhydroxycholesterol, an endogenous CYP3A4 metabolite ( Wollmann et al, 2017 ). CYP3A4 activity has been shown to correlate with proinflammatory cytokine levels, especially those of IL-1ra, IL-6, and CXCL8 ( Wollmann et al, 2018 ). In addition, the central role of IL-6 in the inhibition of CYP clearance in rheumatoid arthritis has been shown in clinical trials evaluating monoclonal antibodies targeting IL-6 ( Lee, Tripathi, & Morgan, 2017 ; Schmitt et al, 2011 ; Zhuang et al, 2015 ).…”
Section: Pharmacological Consequences Of Inflammation-induced Metabolmentioning
confidence: 99%
“…Inhibition of cytokines production by non-steroidal anti-inflammatory drugs (NSAIDs) or treatment with antibodies against specific cytokines can reverse the reduction of CYP enzymes and the changes in the clearance of propranolol in RA animal models [ 76 , 77 ], confirming that cytokines have an important role in the regulation of CYP enzymes in RA. In humans, it was recently reported that the levels of inflammatory cytokines are negatively associated with CYP3A4 phenotype in RA patients [ 78 ]. On the other hand, in terms of membrane transporters, the mRNA levels of numerous ABC and SLC transporters (e.g., Oatps , Mdr1a , Mrp2 ) are decreased in adjuvant- or collagen-induced arthritis rats [ 75 , 79 ].…”
Section: Aberrant Expression Of Dmes and Transporters In Inflammatory...mentioning
confidence: 99%